2014
DOI: 10.1146/annurev-psych-010213-115110
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Pathways and the Evolution of Human Behavior

Abstract: This review examines the hypothesis that oxytocin pathways--which include the neuropeptide oxytocin, the related peptide vasopressin, and their receptors--are at the center of physiological and genetic systems that permitted the evolution of the human nervous system and allowed the expression of contemporary human sociality. Unique actions of oxytocin, including the facilitation of birth, lactation, maternal behavior, genetic regulation of the growth of the neocortex, and the maintenance of the blood supply to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
459
0
22

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 572 publications
(500 citation statements)
references
References 122 publications
(205 reference statements)
19
459
0
22
Order By: Relevance
“…Interestingly, these structures and the nerves that innervate them were described as part of a system (polyvagal theory) 19 that permits social engagement and communication. 1 In addition, we observed a significant increase in circulating AG, which is called "the hunger hormone, " after OXT treatment that may counterbalance the excess of UAG, which possibly drives anorexia, as discussed in our recent publication. 20 Interestingly, increased gastric ghrelin gene expression after OXT treatment has been recently reported in neonatal pigs.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Interestingly, these structures and the nerves that innervate them were described as part of a system (polyvagal theory) 19 that permits social engagement and communication. 1 In addition, we observed a significant increase in circulating AG, which is called "the hunger hormone, " after OXT treatment that may counterbalance the excess of UAG, which possibly drives anorexia, as discussed in our recent publication. 20 Interestingly, increased gastric ghrelin gene expression after OXT treatment has been recently reported in neonatal pigs.…”
Section: Discussionsupporting
confidence: 58%
“…In humans, "mutual gaze" is the most fundamental manifestation of social attachment. 1 Indeed, we are aware that these changes may have been due to OXT and/or to the support and guidance provided by the expert team to the parents.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our results describe a global parental caregiving brain network that was mainly consistent across parents and involved brain structures implicated in vigilance, salience, reward, motivation, social understanding, and cognitive empathy. These brain structures were linked with oxytocin, the hormone implicated in human and mammalian bond formation (19,20), and with the humanspecific repertoire of parental behavior, indicating that assuming the role of a committed parent and engaging in active care of the young may trigger this global parental caregiving network in both women and men, in biological parents, and in those genetically unrelated to the child. Such findings are consistent with the hypothesis that human parenting may have evolved from an evolutionarily ancient alloparenting substrate that exists in all adult members of the species and can flexibly activate through responsive caregiving and commitment to children's well-being (2).…”
Section: Discussionmentioning
confidence: 99%
“…Only one study compared maternal and paternal brain response to infant cues, reporting mothers' greater amygdala activation, fathers' greater superior-temporal and medialfrontal activation, and maternal and paternal oxytocin's different associations with amygdala vs. cortical activation (18). Oxytocin, a nine-amino acid neuropeptide that underpins the formation of affiliative bonds (19), supports the development of human parental caregiving (20). Research has shown that maternal and paternal oxytocin levels are associated with parent-infant synchrony, which is the parent's careful adaptation of caregiving behavior to infant's social signals (21).…”
mentioning
confidence: 99%
“…The hypothalamic peptide oxytocin (OT) is an evolutionarily ancient neuropeptide implicated in sociality and well-being (3,4) and has been recently proposed as an important molecular substrate for social adaptation (5). The social adaptation model (5) posits that a fundamental function of OT is to promote adaptation to the social environment, by modifying cognitive processes and emotional responses and adjusting behaviors.…”
mentioning
confidence: 99%